Enhancement of electrons confinement in AlGaN/AlN/GaN heterostructure using BGaN buffer with a small B-content. (February 2019) - Han, Tiecheng; Zhao, Hongdong; Peng, Xiaocan
Abstract: Since the small lattice constant a of wurtzite BGaN alloy and the good insulating property of its epitaxial layer, the use of the BGaN with a small B-content (0.005–0.02) as a buffer has potential to be a back-barrier for GaN high-electron mobility transistors (HEMTs). This paper presents an improved BGaN back-barrier HEMT structure (AlGaN/AlN/GaN/BGaN buffer) that does not create parasitic electron channel. The energy-band profile and carrier distribution of the BGaN buffer structure are studied by one-dimensional self-consistent simulation. The results show that the BGaN buffer with a very small B-content can provide a sufficient back-barrier to enhance electrons confinement, the principle of which is similar to the formation of back-barrier of AlGaN buffer. When the channel increases to a certain thickness, the low-density two-dimensional hole gas (2DHG) can even be induced at the GaN/BGaN interface by increasing the B-content from 0 to 0.02. Once the 2DHG is formed, continued increase in B-content would result in higher density 2DHG, while the effect on the energy-band profile, electrons confinement, and two-dimensional electron gas (2DEG) density becomes less pronounced. Highlights: The wurtzite BGaN with a small B-content as a buffer layer has potential to be a back-barrier for GaN-based HEMTs. An AlGaN/AlN/GaN/BGaN heterostructure is theoretically proposed to enhance the electrons confinement. The coexistence of two-dimensional electron gas (2DEG) and two-dimensional holes gas (2DHG).